XIX. yüzyıldan bir Osmanlı Seyahatnamesi: Seyahat-i Asmaî (Metin-İnceleme) - Şahin, Fahriye Nilsun (My University, 2010)
Çalışmanın esasını Asmaî’nin (Yusuf Samih) Seyahat-i Asmaî adlı seyahatnamesinin latin harflerine çevirimi teşkil etmektedir. Ancak daha önce Seyahat-i Asmaî’nin bir seyahatname olması münasebetiyle edebiyat-seyahat ilişkisi ile Türk edebiyatında Avrupa merkezli seyahat eserleri hakkında bilgi verilmiştir. Daha sonra seyahatname; Şehirler, Tarihi Binalar, Sokak ve Bahçeler; Seyahat Vasıtaları; Aile ve Kadın; Din ve Medeniyet; Dil ve Güzel Sanatlar; Yeme İçme Kültürü; Âdetler, Gelenekler, Batıl İnançlar; Tanıdığı Yeni İnsanlar ve Gündelik Hayat alt başlıkları altında kısaca incelenmiştir. Asmaî, Yusuf Samih, seyahatname, Avrupa, yol, yolculuk, medeniyet

The transliteration of the travel writing entitled Seyahat-i Asmaî by Asmaî (Yusuf Samih) into latin alphabet constitutes the main part of this study. However, as the above-mentioned work is an example of travel literature, this study starts with a preliminary which deals with the inter-relationship between literature and travel, including an informative part on the Europe centered travel writing in Turkish Literature. Afterwards, the genre 'travel writing' is briefly analysed under the following subtitles: Cities, Historical Buildings, Streets and Gardens; Travel Vehicles; Family and Women; Religion and Civilization; Language and Fine Arts; Culinary Culture; Traditions, Superstitions, New Acquaintances and Everyday Life. Key Words: Asmaî, Yusuf Samih, travel writing, Europe, route, journey, civilization
Keywords: Osmanlı İmparatorluğu, 1299-1918; Seyahatname